Erythema annulare centrifugum as presenting sign of activation of breast cancer - Ilteris Oguz Topal; Yunus Topal; Aytul Sargan; Hatice Duman; Sule Gungor; Ozgur Emek Kocaturk Goncu; Selver Ozekinci (Sociedade Brasileira de Dermatologia, 2015)
Abstract: Erythema annulare centrifugum is a figurate erythema of unknown etiology. It has been associated with many different entities, including infections, food allergy, drug reactions and malignant neoplasms. Herein, we report a case of erythema annulare centrifugum as presenting sign of activation of breastcancer.